Health benefits and costs of weight-loss dietary counselling by nurses in primary care: a cost-effectiveness analysis. Issue 1 (14th October 2019) - Cleghorn, Christine L; Wilson, Nick; Nair, Nisha; Kvizhinadze, Giorgi; Nghiem, Nhung; McLeod, Melissa; Blakely, Tony
Abstract: Objective: We aimed to estimate the cost-effectiveness of brief weight-loss counselling by dietitian-trained practice nurses, in a high-income-country case study. Design: A literature search of the impact of dietary counselling on BMI was performed to source the 'best' effect size for use in modelling. This was combined with multiple other input parameters (e.g. epidemiological and cost parameters for obesity-related diseases, likely uptake of counselling) in an established multistate life-table model with fourteen parallel BMI-related disease life tables using a 3 % discount rate. Setting: New Zealand (NZ). Participants: We calculated quality-adjusted life-years (QALY) gained and health-system costs over the remainder of the lifespan of the NZ population alive in 2011 ( n 4·4 million). Results: Counselling was estimated to result in an increase of 250 QALY (95 % uncertainty interval −70, 560 QALY) over the population's lifetime. The incremental cost-effectiveness ratio was 2011 $NZ 138 200 per QALY gained (2018 $US 102 700). Per capita QALY gains were higher for Māori (Indigenous population) than for non-Māori, but were still not cost-effective. If willingness-to-pay was set to the level of gross domestic product per capita per QALY gained (i.e. 2011 $NZ 45 000 or 2018 $US 33 400), the probability that the intervention would be cost-effective was 2 %. Conclusions: The study provides modelling-level evidence that brief dietary counselling for weight loss in primary care generates relatively small health gains at the population level and is unlikely to be cost-effective.